KINERJA TIM AKREDITASI PADA PROSES AKREDITASI PROGRAM STUDI (Studi Kasus: Tim Akreditasi Program Studi di STKIP YPM Bangko) - Mardalena Mardalena (Universitas Batanghari Jambi, 2018)
Performance of human resource becomes one of the significant role in the running of the organization. This research, the human resource are the personnel team acreditation of English education study program in STKIP YPM Bangko. Personel team is the central part in deciding the readiness of studi program in preparing the acreditation. Acreditaiton team consist group of lecturers in ensuring the process of acreditation Tim akreditasi adalah sekumpulan orang yang diharapkan untuk menjamin kesiapan prodi pada proses akreditasi dalamand later on in getting excellent result of acreditation by National Institution of Acreditation. in short, performance of acreditation team will determine the result of the acreditation. Key Words: Work Performance, Human Resource, Accreditation